Sobre los paradigmas en la investigación lingüística - Casas Navarro, Raymundo (2007)
In this paper, we will argue that the metatheoretical notion of paradigm is a useful concept to account for the development of linguistic research. To this end, we will first elucidate the notion of paradigm on the basis of Thomas Kuhn's ideas (1970, 2000). Then, we will schematically present three research paradigms in linguistics: structuralist linguistics, Chomskyan generativism and cognitive grammar. Our presentation will touch on the ontological commitments that define the nature of linguistic research according to each paradigm. Finally, as a corollary of our epistemological reflections, we will draw some conclusions on the issue of interdisciplinarity in the sciences.